The age of empires : Mesopotamia in the first millennium BC - Joannès, Francis (Edinburgh University Press, 2004)
This is a concise introduction to the history of the ancient Near East during the last millennium bc: Phoenicia, Palestine, the Neo-Assyrian and Neo-Babylonian empires, the Persian Achaemenid empire, the empire of Alexander, and the vast Persian Seleucid empire founded by Seleucus around 300 bc and defeated by Pompey for Rome in 64 bc. The book focuses on political history, on the sources and shifts of power and the individuals who wielded it. It also introduces the student to the principal aspects of the religious, social and economic history of the region.The narrative is succinct, backed up by summary tables and maps, and enlivened by lengthy "ations from contemporary documents. The latter are frequently used to illustrate specific case studies. The book ends with a chronology and glossary, as well as an adapted further reading list.